THE EFFECT OF IMPLEMENTATION OF SUPERVISOR SUPERVISION COMMUNICATIONS ON IMPROVING THEMATIC LEARNING IN SD GUGUS II, KELARA DISTRICT, JENEPONTO REGENCY - Kamaluddin, Kamaluddin (Jurnal Diskursus Islam, 2021)
Communication is essential in life. No exception for supervisors should have communication skills. In Jeneponto Regency, the application of the thematic learning model requires supervisors who have communication skills. The research shows a positive effect on increasing thematic learning in SD Gugus II, Kelara District, Jeneponto Regency. The magnitude of the impact is 25, 90%, and other variables determine the rest.